Transforming Transportation in India: Exploring the Challenges and Opportunities of Electric Vehicles - Kishor Jadhav; Shital Jadhav; Prajakta Waghmode; Bhakti Kadam; Shraddha Pandhe; Rahul K. Shinde (International Journal of Energy and Thermal Applications, 2024)
They also help lessen the impact of ozone-depleting substances and support the widespread adoption of renewable energy. Although significant research has focused on EV features, performance, and charging infrastructure, challenges in production and network modeling persist. This paper provides an overview of various EV technologies, including EVs, hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and battery electric vehicles (BEVs), and evaluates their market penetration rates. It explores various modeling approaches and optimization techniques, addressing key challenges like insufficient charging infrastructure, especially in a developing country like India. The study highlights the emerging concept of vehicle-to-grid (V2G) technology as a potential additional power source when renewable energy is unavailable. The findings emphasize the unique characteristics of EVs in terms of mobility and their potential to reduce CO2 emissions. Additionally, the paper examines the opportunities and challenges in the Indian EV market, focusing on economic, social, technical, and environmental factors, and provides recommendations for overcoming these barriers to promote EV adoption in India.
Keywords: EV adoption in India; EV technologies; emissions